2006
DOI: 10.1016/j.physletb.2006.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and interference in the dissociation of halo nuclei

Abstract: The dissociation of halo nuclei through their collision with light and heavy targets is considered within the Continuum Discretized Coupled Channels theory. We study the one-proton halo nucleus 8 B and the one-neutron halo nucleus 11 Be, as well as the more normal 7 Be. The procedure previously employed to extract the Coulomb dissociation cross section by subtracting the nuclear one is critically assessed, and the scaling law usually assumed for the target mass dependence of the nuclear breakup cross section i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
73
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 44 publications
9
73
2
Order By: Relevance
“…The interference is so strong at low energy that it almost doubles the Table 1 one sees also that for both projectiles the total nuclear breakup cross sections are always of the same order of magnitude than the recoil Coulomb breakup on a heavy target but much smaller than the direct Coulomb and the total Coulomb cross sections. Thus we confirm what has already been suggested by other authors [5,10,11], on why in the past, calculated nuclear breakup of a proton has been found comparable to or even larger than the Coulomb breakup. The misinterpretation was simply due to an underestimate of the direct Coulomb breakup due to both the dipole approximation and its treatment to first order and to the fact that interference effects were overlooked.…”
Section: Resultssupporting
confidence: 93%
“…The interference is so strong at low energy that it almost doubles the Table 1 one sees also that for both projectiles the total nuclear breakup cross sections are always of the same order of magnitude than the recoil Coulomb breakup on a heavy target but much smaller than the direct Coulomb and the total Coulomb cross sections. Thus we confirm what has already been suggested by other authors [5,10,11], on why in the past, calculated nuclear breakup of a proton has been found comparable to or even larger than the Coulomb breakup. The misinterpretation was simply due to an underestimate of the direct Coulomb breakup due to both the dipole approximation and its treatment to first order and to the fact that interference effects were overlooked.…”
Section: Resultssupporting
confidence: 93%
“…What is first done (wrongly) is to ignore σ bu inter f erence , and consider σ bu N to scale linearly with the mass number of the target nucleus. We rely on a recent study of this topic, especially with regards to the dependence on the target mass, made at higher energies, [3,4]. According to this study, the nuclear breakup cross section behaves at a given value of the bombarding energy, E Lab as,…”
mentioning
confidence: 99%
“…According to this study, the nuclear breakup cross section behaves at a given value of the bombarding energy, E Lab as, In the above P 1 and P 2 , given in mb, are functions of the bombarding energy, and structure of the projectile. This formula, well substantiated by extensive continuum discretized coupled channels calculation in [3], is used to estimate the nuclear cross section for breakup on a heavy target, given the experimental value of the cross section on a light target such as 12 C, where the Coulomb breakup is usually much smaller. We mention here that [5] also derive a scaling law, but finds a different dependence on the target mass.…”
mentioning
confidence: 99%
See 2 more Smart Citations